Disseminated spinal myxopapillary ependymoma in an adult at initial presentation: A case report and review of the literature. (October 2014) - Straus, David; Tan, Lee A.; Takagi, Ippei; O'Toole, John E.
Abstract Disseminated spinal myxopapillary ependymoma (MPE) is extremely rare in adults. We report a 63-year-old man with chronic low-back pain found to have multiple MPEs in the thoracic, lumbar and sacral spine. Diagnostic and management strategies of disseminated MPE are discussed with a review of pertinent literature.